Identification of the Causes Waste Material in the Railway Bridge Construction Project - Malaiholo, David; Prihartanto, Rusman; Puruhita, Hana Wardani (ASTONJADRO, 2024)
Material is one of the important components that has a close influence on the cost of a project, so with a large amount of construction material waste, it can be said that there is an overrun in the financing sector. In addition, the remaining construction materials can produce a high percentage of environmental pollution. Residual material or construction waste is something that is never separated from a project development. The existence of leftover materials can have a negative effect on the environment around the construction project. The remaining material can be interpreted as part of the material that has not been used resulting from the process of construction, repair, change or any item produced from the process, or an accident that cannot be directly used in that place without any further treatment. The railway bridge construction project certainly requires various types of materials, when viewed from the concept for the use of large materials, the more the remaining materials that exist or become construction waste. This research aims to determine the quantity of material waste generated from the construction of the railway bridge and analyze the factors that cause material waste in the railway bridge construction project. This research method uses observation and interview techniques and is supported by data obtained from the research location. The results of this study show that the largest percentage of waste cost during the railway bridge construction project came from K300 concrete material for retaining walls in the amount of 16.714% or Rp. 6,283,720.00. The source of the cause of the remaining material where the factors are generated from project actors, design, measurement/calculation, management, implementation and procurement/handling of materials.